Incidence of Seizures in ESRD Patients on Hemodialysis - Mashal, Sara Pervez, Ayesha Javaid, Hira Wakil, Numan Shah, Yousaf Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The kidneys filtration waste and excess water from your blood as urine. CKD when the GFR of the patient less than 15ml/min. ESKD is the final stage of CKD. HD is a common renal replacement therapy for ESRD patients. CKD may have many effects on nervous system and manifest as headache, seizure and DDS etc. Seizure is one of the complication of HD. Seizures are changes in the brain’s electrical activity. The study was conducted to assess the occurrence of seizure in hemodialysis patient and to analyze the possible causes of seizure in renal failure patient during hemodialysis. Methods and Materials: In this cross-sectional study, collected 202 samples for assessing the causes of seizures in patients on HD. In this study the selected ESRD patients with different types of seizures and causes which leads to HAS. To evaluate the occurrence of seizures in hemodialysis patients, individuals were thoroughly examined. Results: Among total of 202 hemodialysis patients, 16 patients were found suffered with seizures. Out of 16 patients, 14 patients were agreed to participate in the current study. The finding of this study showed that there are many causes of HAS but some are the most shown in this study. This study revealed that hypoglycemia, hypocalcemia (hyperparathyroidism), uremic encephalopathy, hyponatremia and use of erythropoietin for the cure of anemia in the dialysis patients are the most common causes of seizures seen. Conclusion: Some neurologic manifestations such as seizure, headache and developmental delay in patients with ESRD are seen. HAS is an important complication of HD. Moreover, treated properly in these cases for decrease of morbidity and mortality and there treatment should be told to medical professionals. Keywords: Hemodialysis, ESRD, Incidence, Seizures